Encouraging or Obstructing? Assessing Factors That Impact Faculty Engagement in Undergraduate Research Mentoring - Davis, Shannon N.; Jones, Rebecca M.; Mahatmya, Duhita; Garner, Pamela W. (Frontiers in Education, 2020)
At colleges and universities around the world, faculty serve a critical role in supporting the well-documented practice of undergraduate research, scholarly and creative activity. Using unique data from an online survey of faculty members (n = 223) at three colleges and universities in the United States, we investigate the individual and institutional factors that facilitate or inhibit faculty members’ willingness to provide undergraduate students with research opportunities. We focus our quantitative analysis on individual and institutional variables associated with faculty participation. Our work confirms prior qualitative research, indicating the significance of institutional support for faculty engagement in undergraduate research mentoring.